2014
DOI: 10.3389/fnsys.2014.00101
|View full text |Cite
|
Sign up to set email alerts
|

Translational studies of goal-directed action as a framework for classifying deficits across psychiatric disorders

Abstract: The ability to learn contingencies between actions and outcomes in a dynamic environment is critical for flexible, adaptive behavior. Goal-directed actions adapt to changes in action-outcome contingencies as well as to changes in the reward-value of the outcome. When networks involved in reward processing and contingency learning are maladaptive, this fundamental ability can be lost, with detrimental consequences for decision-making. Impaired decision-making is a core feature in a number of psychiatric disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 203 publications
(233 reference statements)
1
89
0
1
Order By: Relevance
“…With an impaired habit-breaking phenotype present in numerous psychiatric disorders (Griffiths et al, 2014), and wide-spread use of the abused drugs in the general populace, our findings suggest that therapeutic targeting of the endocannabinoid system is a viable option for restoration of goal-directed control.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…With an impaired habit-breaking phenotype present in numerous psychiatric disorders (Griffiths et al, 2014), and wide-spread use of the abused drugs in the general populace, our findings suggest that therapeutic targeting of the endocannabinoid system is a viable option for restoration of goal-directed control.…”
Section: Discussionmentioning
confidence: 88%
“…However, the transition between habitual and goal-directed control provides the capacity to perform the same action based on updated consequences. Difficulties with stopping habits and shifting to goal-directed control underlie numerous neuropsychiatric disorders that display impaired decision-making (Dias-Ferreira et al, 2009; Graybiel, 2008; Griffiths et al, 2014) including obsessive-compulsive disorder (BurguiĂšre et al, 2015; Gillan et al, 2011) and addiction (Belin et al, 2013; Goldstein and Volkow, 2011). However, our understanding of specific molecular mechanisms and circuitry involved in controlling action shifting remains limited.…”
mentioning
confidence: 99%
“…Indeed, an aberrant experience of voluntary control, or “sense of agency”, appears to be a common characteristic of psychiatric illness: Schizophrenic individuals differ from healthy controls both in the degree of intentional binding – a perceived compression of the time interval between voluntary actions and their consequences – and in reported self- vs. external attributions of decision outcomes2930313233. Although operational definitions of agency and volition differ substantially across these reports, and while related research suggests that schizophrenic and depressed individuals may be more fundamentally impaired with respect to goal-directed learning and performance3435, the apparent role of instrumental choice in psychopathology suggests that a better understanding of the perceived value of flexible instrumental control in healthy individuals may be of significant clinical interest.…”
Section: Discussionmentioning
confidence: 96%
“…The basolateral amygdala (BLA), in particular, form strong reciprocal connections with the medial and orbital PFC both directly and indirectly, through the mediodorsal thalamic nucleus (which communicates with the PFC; Price et al, 1996). A series of studies in humans, monkeys, and rodents have indicated that the network between medial PFC, orbital PFC, and BLA is critical for the evaluation of the stimulus that would follow a chosen action (Baxter and Murray, 2002; Griffiths et al, 2014). Activation of human BLA neurons in response to food items scales with their monetary value (Jenison et al, 2011).…”
Section: The Dopaminergic System In Frontostriatal Circuitsmentioning
confidence: 99%